2021
DOI: 10.1161/circinterventions.121.011314
|View full text |Cite
|
Sign up to set email alerts
|

Compared Outcomes of ST-Segment–Elevation Myocardial Infarction Patients With Multivessel Disease Treated With Primary Percutaneous Coronary Intervention and Preserved Fractional Flow Reserve of Nonculprit Lesions Treated Conservatively and of Those With Low Fractional Flow Reserve Managed Invasively: Insights From the FLOWER-MI Trial

Abstract: Background: In patients with ST-elevation myocardial infarction (STEMI) and multivessel disease, percutaneous coronary intervention (PCI) for non-culprit lesions guided by FFR is superior to treatment of the culprit lesion alone. Whether deferring non-culprit PCI is safe in this specific context is questionable. We aimed to assess clinical outcomes at one-year in STEMI patients with multivessel coronary artery disease and an FFR-guided strategy for non-culprit lesions, according to whether or not ≥… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 22 publications
2
14
0
2
Order By: Relevance
“…Subsequently, a substudy of the FLOWER-MI found that patients in the FFR guidance arm with ≥1 PCI had lower event rates at 1 year, compared with patients with a deferred PCI. 4 These findings align with a recent large patient-level metanalysis 5 ( n = 8579) that found increased event rates associated with an FFR-based deferral of revascularization of NCLs in ACS, compared with stable patients, pointing to either suboptimal performance of non-culprit FFR in STEMI patients or a protective effect of PCI in NCLs with rupture-prone vulnerable plaques. Overall, PCI of severely stenotic NCLs in ≥2.0 mm diameter arteries is indicated for STEMI patients, regardless of the FFR status, when technically feasible.…”
Section: Non-culprit Lesion Revascularization In St-segment Elevation...supporting
confidence: 83%
“…Subsequently, a substudy of the FLOWER-MI found that patients in the FFR guidance arm with ≥1 PCI had lower event rates at 1 year, compared with patients with a deferred PCI. 4 These findings align with a recent large patient-level metanalysis 5 ( n = 8579) that found increased event rates associated with an FFR-based deferral of revascularization of NCLs in ACS, compared with stable patients, pointing to either suboptimal performance of non-culprit FFR in STEMI patients or a protective effect of PCI in NCLs with rupture-prone vulnerable plaques. Overall, PCI of severely stenotic NCLs in ≥2.0 mm diameter arteries is indicated for STEMI patients, regardless of the FFR status, when technically feasible.…”
Section: Non-culprit Lesion Revascularization In St-segment Elevation...supporting
confidence: 83%
“…In a subset analysis of the FLOWER MI trial, patients who underwent PCI for 1 or more non-culprit stenoses had lower event rates at 1 year, compared with patients with deferred PCI based on a FFR > 0.80, suggesting that deferring lesions that appear significant by visual estimation but with FFR > 0.80 in the setting of STEMI may not be the correct course of action. 27 Lee et al 28 reported that non-culprit stenoses in patients with an FFR > 0.8 in patients with ACS were associated with more than twofold higher rate of MACE than non-culprit stenoses with FFR > 0.8 in patients with stable coronary disease. Those findings are also consistent with our understanding of the pathobiology of vulnerable plaque whereby plaque volume, composition and dynamic behavior is more important than stenosis physiologic severity in predicting MI, particularly in vulnerable patients.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are consistent with the preponderance of evidence regarding the limited utility of FFR guided revascularization of non‐culprit stenoses in patients with STEMI. In a subset analysis of the FLOWER MI trial, patients who underwent PCI for 1 or more non‐culprit stenoses had lower event rates at 1 year, compared with patients with deferred PCI based on a FFR > 0.80, suggesting that deferring lesions that appear significant by visual estimation but with FFR > 0.80 in the setting of STEMI may not be the correct course of action 27 . Lee et al 28 reported that non‐culprit stenoses in patients with an FFR > 0.8 in patients with ACS were associated with more than twofold higher rate of MACE than non‐culprit stenoses with FFR > 0.8 in patients with stable coronary disease.…”
Section: Discussionmentioning
confidence: 99%
“…Cerrato and Escaned report that the conclusions of their patient-level meta-analysis of cohorts of patients with either stable angina pectoris or acute coronary syndrome in whom percutaneous coronary intervention was deferred on the basis of fractional flow reserve measurements are in line with our findings from the FLOWER-MI trial (FLOW Evaluation to Guide Revascularization in Multi-Vessel ST-Elevation Myocardial Infarction). [1][2][3] In fact, in patients with deferred percutaneous coronary intervention, they observed a higher major adverse cardiac events (MACE) rate after acute coronary syndrome, compared with MACE occurring in stable patients (hazard ratio, 1.72 [95% CI, 1.17-2.53]); however, in contrast with what we observed, MACE rates were lower in patients with acute coronary syndrome with deferred percutaneous coronary intervention (52/1166, 4.46%) versus those in whom percutaneous coronary intervention was actually performed (62/952, 6.51%; Table ). We, therefore, do not understand why the authors now conclude from their analysis that deferring revascularization in nonculprit lesions with fractional flow reserve >0.80 was associated with an increased risk of events.…”
Section: Letter To the Editormentioning
confidence: 99%